The recent impact of government transfers on poverty in Honduras and alternatives to enhance their effects - Rafael Guerreiro Osório (International Poverty Centre (IPC), 2008)
This paper characterises income poverty in Honduras during the first half of 2007, and assesses the impact that some government transfers have had on it. The characterisation of income poverty shows that it is possible to eradicate poverty in Honduras solely through redistribution, despite its being a low-income country. The analysis of the incidence and impact of government transfers reveals that they do reach the poor, but that they are not very effective in reducing the poverty headcount ratio or in alleviating poverty by reducing its intensity and severity. Nonetheless, the counterfactual simulations presented here show that improvements in targeting and increases in the amount transferred could significantly enhance the impact of government transfers on poverty in Honduras.
Keywords: 330; Armut; Armutspolitik; Öffentlicher Transfer; Honduras